A SIP to a gulp: graphicons as social information in text-based computer-mediated communication - Gao, Yang (Nanyang Technological University, 2023)
With the rapid advancement of communication technology, the landscape of computer-mediated communication (CMC) has gone through profound changes, especially in text-based interactions. Graphicons (i.e., a mix of Graphic icons, Herring & Dainas, 2017) such as emoticons, emoji, stickers, and animated GIFs have transformed the experience of text-based CMC into a hyperpersonal communication experience "far richer when mediated than in-person" (Sundar, 2008, p. 59). Drawing on the Social Information Processing theory (Walther, 1992), this project utilizes a mixed-method approach with an exploratory sequential design (Creswell, Clark, Gutmann, & Hanson, 2003) to examine the role and effect of Graphicons as nonverbal cue systems during text-based interpersonal interactions. Based on the findings of semi-structured focus group discussions with Chinese university students (Study 1, n = 53), Graphicons are argued to be a critical nonverbal cue system in text-based CMC that serves six primary functions. These functions parallel those of in-person, nonverbal behaviors (Burgoon, Manusov, & Guerrero, 2016). Rich description from qualitative data permits an opportunity to look at the propositions of the SIP theory on a microlevel and to explore users’ cue accommodation process when multiple cue systems are available in the channel. Expanding upon prior research, the concept of Graphicon richness is introduced as a fundamental characteristic that brings together diverse Graphicon types. The conceptualization elucidates the extent to which Graphicons possess the potential to convey socially significant cues, and several influential characteristics have been identified. Study 2, a single factor experiment with three conditions (n = 161), is designed to examine the differential impacts of text and Graphicons (and high vs. low richness) on relational communication. Different uses of Graphicons were hypothesized to affect communicators’ perceptions of formality, immediacy, involvement, and composure towards their partners. The experiment findings partially supported the hypotheses, that is, mediated interactions with Graphicons are perceived to be more involved and less formal than interactions with verbal messages alone. The pattern of results for planned comparisons suggests that the meaningful changes in perceived relational communication come about from the use Graphicons – any Graphicons – compared to text only. Both qualitative data (FGD themes) and quantitative data (experiment results) were discussed and integrated to provide a more comprehensive description of the social information exchange process in cue-enriched CMC.